Use of electrostatic gridded lenses in the laser ion source at CERN - Derbilov, V.I.; Ostroumov, P.N.; Kugler, H.; Lisi, N.; Meyer, C.; Scrivens, R. (Вопросы атомной науки и техники, 1999)
The GEL LEBT provides high efficiency beam transport and matching to the RFQ acceptance in the 4-dimensional phase space. The rms emittance growth is relatively small even for 60 kV extraction voltage. The number of particles occupying the 4-D RFQ acceptance strongly depends from the beam emittance at the entrance of the GEL LEBT. In most realistic case with the input emittance equal to the measured one, which is 320 p×mm×mrad (4×rms emittance) the number of particles inside the 4-D space with the projection emittance of 200 p×mm×mrad is 38% at the entrance and 35% at the output of GEL LEBT, which means that LEBT does not practically destroy beam emittance. The experimental value of the yield to the double aperture is 35% and confirms the expected performance of the GEL LEBT.